2007
DOI: 10.2478/v10035-007-0017-7
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in the Aged

Abstract: After accidents, elderly patients (aged 75 years and older) have been demonstrated to have increased mortality rates after trauma, however, the prognosis of those patients surviving their hospitalization is unknown. We hypothesized that surviving elderly patients would also have decreased functional outcomes. The aim of the study. This study examined the outcome of elderly patients exposed to varying trauma relative to all trauma patients. Material and methods. This was a retrospective study of 5046 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, several studies have shown that there is a correlation between age, mortality and utilisation of health services. [8][9][10] Click HERE for more articles at the Annals, Academy of Medicine, Singapore homepage This study aimed to compare and describe serious trauma in elderly and young patients in an acute tertiary hospital over a 12-year period. It also investigated rates of adverse complications and length of stay (LOS) in both groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that there is a correlation between age, mortality and utilisation of health services. [8][9][10] Click HERE for more articles at the Annals, Academy of Medicine, Singapore homepage This study aimed to compare and describe serious trauma in elderly and young patients in an acute tertiary hospital over a 12-year period. It also investigated rates of adverse complications and length of stay (LOS) in both groups of patients.…”
Section: Introductionmentioning
confidence: 99%